Analisis In Vitro Aktivitas Antioksidan Ekstrak Aseton dari Ranting Horsfieldia macrothyrsa Menggunakan Beragam Metode: In Vitro Analysis of Antioxidant Activity of Horsfieldia macrothyrsa Twig Acetone Extract Using Various Methods - Asnah, Nur; Megawati, Megawati; Parbuntari, Hesty (Jurnal Sumberdaya Hayati, 2024)
Horsfieldia macrothyrsa (Miq) Warb. is a plant that contains secondary metabolite compounds that can act as antioxidants. This research aims to determine the antioxidant potential of the acetone extract of the H. macrothyrsa plant by looking at the IC50 value. Twigs of the H. macrothrysa plant were extracted using the maceration method using acetone solvent. The results of the antioxidant activity test using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method showed very strong antioxidant activity with an IC50 value of 6.348 µg/ml whereas the IC50 value of the standard antioxidant quercetin is and quercetin 1.261 µg/ml. In antioxidant testing using the ABTS (2,2-azinobis (3-ethylbenzothiazoline-6-sulfonate) method, an IC50 value of 12,772 µg/ml was obtained and FRAP (Ferric Reducing Antioxidant Power) obtained an IC50 value of 7,511 µg/ml. Based on the results, it can be concluded that the acetone extract of H. macrothrysa plant twigs has very strong antioxidant activity towards reducing DPPH (2,2-diphenyl-1-picrylhydrazyl) compared to using the ABTS and FRAP methods.